Temperature‐driven wear behavior of Si3N4‐based ceramic reinforced by in situ formed TiC0.3N0.7 particles. Issue 7 (9th January 2019) - Liu, Jiongjie; Yang, Jun; Zhu, Shengyu; Cheng, Jun; Yu, Yuan; Qiao, Zhuhui; Liu, Weimin
Abstract: Si3 N4 as a structural ceramic is desirable for applications in spacecraft, transportation, and energy, but its poor high‐temperature properties still do not satisfy the actual requirements. Here, a TiC0.3 N0.7 reinforced Si3 N4 ceramic is successfully designed and fabricated via the high‐temperature nitridation of TiC x . It is found that TiC0.3 N0.7 grains with the size of 1‐2 μm are uniformly dispersed in the Si3 N4 matrix and show a firm bond with substrate. Compared with pure Si3 N4, the doping of harder TiCN phase can effectively improve ceramic's hardness and fracture toughness at a certain temperature. Importantly, the ceramic material displays extraordinary wear resistance across a wide temperature range (eg, the wear rate of TiC0.3 N0.7 containing Si3 N4 over 63 times and 178 times better than pure Si3 N4 at 600 and 900°C, respectively). More broadly, a correlation between wear mechanism and temperature is established, and the result shows that the mechanical strength and tribochemical oxidation as two key factors determine the wear behavior of the material. These results developed here can provide a springboard for preparation and optimization of multiphase ceramics that serve under high‐temperature conditions.